Drugačije izražene miRNI u plazmnim uzorcima imunoloških trombocitopenih purpura pacijenata i njegove kliničke značajnosti - Feng, Yue; Yao, Yuqian; Zhao, Hemeng; Fang, Yafei (Journal of Medical Biochemistry, 2025)
Objective: Current work has been designed to explore the abnormal expression of miRNAs in plasma samples of patients with immune thrombocytopenic purpura (ITP) to provide more guidance for clinical doctors. Methods: Bioinformatic analysis was performed using the GSE80401 chip. The study subjects were recruited from the First People’s Hospital of Lianyungang between May 2021 and December 2022. 48 ITP patients admitted in intensive care unit were finally enrolled. miRNAs levels have been examined using real-time polymerase chain reaction method. All data was analyzed using SPSS 22.0 software. The potential diagnosis value of the significantly up-regulated and down-regulated miRNAs have been evaluated using receiver operator characteristic (ROC) curve. Results: We performed bioinformatical analysis on GSE80401 chip, and have identified the differently expressed miRNAs in ITP patients compared to the controls, and results of heat map showed the results. GO and pathway analysis showed the process that the diffusely expressed miRNAs involved. Next, results of RT-qPCR analysis showed the levels of miR-877-3p, miR-425-3p, miR-122-5p, miR-1281 as well as miR-1825 significantly increased, while the levels of miR-3945, miR-4430, miR-3158-5p, miR-3131 as well as miR-4655-3p markedly decreased in plasma samples of ITP patients in comparison with the controls. Finally, results showed that the area under the ROC curve of miRNAs were as follow: miR-877-3p, 0.9349, miR-425-3p, 0.8607, miR-1281, 0.7131, miR-1825, 0.8928, miR-3945, 0.8459, miR-4430, 0.8112, miR-3158-5p, 0.6059, miR-3131, 0.8989, suggesting that the above miRNAs may serve as biomarkers for distinguishing the ITP patients with healthy controls. Conclusion: miRNAs may have predictive value in the diagnosis of ITP. The results of current work may provide new clues for the pathogenesis of ITP, which in turn provides new theoretical basis and therapeutic tools for the clinical diagnosis and treatment of ITP.